THE EFFECT OF LEADERSHIP STYLE, WORKLOAD AND FACILITIES ON EMPLOYEE PERFORMANCE AT CV. ISTANA MOBIL KOTA TEBING TINGGI - Tiara Br. Purba; Salsa Nabilla; Aisyah Siregar; Nursaimatussaddiya (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine whether Leadership Style, Workload and Facilities affect Employee Performance at CV. Istana Mobil Tebing Tinggi City. The research method used in this study is a quantitative method. The population in this study were employees of CV. Istana Mobil Tebing Tinggi City totaling 35 people with details of 15 employees in the car wash section and 20 employees in the service section. The data analysis tool used in this study was SPSS (Statistical Packpage for the Social Sciences). The conclusion of the study shows that Leadership Style affects Employee Performance at CV. Istana Mobil Tebing Tinggi City, Workload does not affect Employee Performance at CV. Istana Mobil Tebing Tinggi City, Facilities affect Employee Performance at CV. Istana Mobil Tebing Tinggi City, Leadership Style, Workload and Facilities have a simultaneous effect on Employee Performance at CV. Istana Mobil Tebing Tinggi City.